Simultaneous presence of juxtafacet cyst and ligamentum flavum hematoma - Ak, Hakan; Vural, Sevilay (Asian Journal of Neurosurgery, 2020)
Juxtafacet cysts and ligamentum flavum hematoma have the potential to cause acute root or spinal cord compression despite their low incidences. Their simultaneous presence with acute nerve compression has not been reported. Herein, we present a case who reported with low back and leg pain to the emergency department.
Keywords: Juxtafacet cyst; ligamentum flavum hematoma; low back pain; lumbar spine